Giant Intrapulmonary Teratoma: A Rare Case - Rayees Ahmad Dar; Majid Mushtaque; Sabiya Hamid Wani; Rayees Ahmed Malik (Case Reports in Pulmonology)
Teratomas are tumors composed of tissues derived from more than one germ cell line. Pulmonary teratomas are rare and commonly involve the upper lobe of the left lung. Criteria for pulmonary origin are the exclusion of a gonadal or other extragonadal primary site and origin entirely within the lung. We report a case of a giant pulmonary teratoma in a 2-year-old male child and review the relevant literature.